Increasing The Understanding of Youth Groups about the Sexual Violence Crime Law The Initial Milestone in the Elimination of Sexual Violence in the Community of Sukasari Village, East Bogor - Herli Antoni; Asmak Ul Hosnah; Sapto Handoyo; Mustika Mega Wijaya; Nazarudin Latif; Yennie K Milono (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The Sexual Violence Law (UU TPKS) which contains important and strategic legal politics and is a breakthrough in legal renewal and protection of the community, this regulation is expected to answer various problems of sexual violence that continue to occur in various modes. The results of the 2021 National Women's Life Experience Survey conducted by the Ministry of PPPA, the Central Statistics Agency and the Demographic Institute of the University of Indonesia found that 1 in 19 women (aged 15-64 years) had experienced sexual violence other than their partners. Of course, with the existence of these regulations and regulations, it is hoped that it will be able to be accepted by the community, especially among young people as the spearhead of the civilization and progress of the Indonesian nation, especially the youth group in the Sukasari village environment, this is an encouragement so that young people in the Sukasari village environment understand and are able to be protectors for themselves and their closest environment about the latent dangers of sexual violence so as not to become victims of this crime, Of course, with this purpose, the method that will be applied is to socialize the newly legalized laws and regulations regarding the crime of sexual violence, and to assist pinyitas and form an integrated service post for assistance to youth and the community. From this effort, it is hoped that youth groups and the community will have an understanding and increase knowledge of laws and regulations related to sexual violence, on the other hand, the existence of an integrated service post is able to accompany the community and youth who are victims as well as the community can be actively involved as a moral movement for the prevention of sexual violence. this is certainly a great hope for the community to be able to implement it in daily life in the community.